Contract-based slicing - Cruz, Daniela da (2010)
In the last years, the concern with the correctness of programs has been leading programmers to enrich their programs with annotations following the principles of design-by-contract, in order to be able to guarantee their correct behaviour and to facilitate reuse of veriﬁed components without having to reconstruct proofs of correctness. In this paper we adapt the idea of speciﬁcation-based slicing to the scope of (contract-based) program veriﬁcation systems and behaviour speciﬁcation languages. In this direction, we introduce the notion of contract-based slice of a program and show how any speciﬁcation-based slicing algorithm can be used as the basis for a contract-based slicing algorithm.